2009
DOI: 10.1021/nn900756s
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Light-Harvesting Ruthenium Sensitizer for Thin-Film Dye-Sensitized Solar Cells

Abstract: A high molar extinction coefficient heteroleptic ruthenium complex, incorporating an electron-rich hexylthio-terminal chain, has been synthesized and demonstrated as an efficient sensitizer for dye-sensitized solar cells. With this new sensitizer excellent power conversion efficiency is 11.5% and 4.7% obtained under an irradiation of full sunlight (air mass 1.5 global) in combination with a volatility electrolyte and solid state hole transporting material, respectively. The devices with low volatility electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
706
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,237 publications
(720 citation statements)
references
References 34 publications
11
706
1
2
Order By: Relevance
“…10), stands out for its conjugated thiophene chains and high molar extinction coefficient, yielding a PCE of 11.5%. 84 The synthetic focus later shifted towards other organic sensitizers, largely driven by the need to produce Ru-free materials in order to bypass not only the limitation of their high cost, but also their usually poor absorption extinction coefficients. Many different organic dyes, such as indolenes, perylenes, squarines, donor-acceptor (D-A) dyes, have been reported over the years, but efficiencies consistently remain in the range of 6-8% 85 with a few exceptions.…”
Section: Organic Dyementioning
confidence: 99%
“…10), stands out for its conjugated thiophene chains and high molar extinction coefficient, yielding a PCE of 11.5%. 84 The synthetic focus later shifted towards other organic sensitizers, largely driven by the need to produce Ru-free materials in order to bypass not only the limitation of their high cost, but also their usually poor absorption extinction coefficients. Many different organic dyes, such as indolenes, perylenes, squarines, donor-acceptor (D-A) dyes, have been reported over the years, but efficiencies consistently remain in the range of 6-8% 85 with a few exceptions.…”
Section: Organic Dyementioning
confidence: 99%
“…DSSCs based on TiO 2 have been extensively studied and their efficiency reaches as high as 11% [3,4]. ZnO material with a wide-band gap semiconductor is considered as an alternative to TiO 2 for the photoanode in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] For the sensitizers, it has been reported that Ru(II) metal complexes exhibit superior, double-digit efficiencies under AM 1.5 global illumination. [10][11][12][13][14][15] However, the thiocyanate ligands incorporated in typical Ru(II) sensitizers are believed to provide the weakest bonding of the whole molecule, making the sensitizers and, hence, the as-fabricated solar cells somewhat unstable under excessive thermal stress and/or light soaking. 16 This latent inferiority has triggered studies attempting to replace the thiocyanate ligands of Ru(II) sensitizers with different chelating anions, such as diketonate, 17 picolinate 18 and heteroaromatic cyclometalates, 19,20 among which the cyclometalates seem to be the most promising ancillary ligands.…”
Section: Introductionmentioning
confidence: 99%